Arylnaphthalene lignans with a focus Linum species: a review on phytochemical, biotechnological and pharmacological potential - Rada Nedelcheva; Yancho Zarev; Rositsa Mihaylova; Ekaterina Kozuharova; Georgi Momekov; Iliana Ionkova (Pensoft Publishers, 2024)
Lignans are a large group of dimeric phenylpropanoids with a long and distinguished history of medicinal use in the ancient cultures of many peoples. The two main groups, -aryltetralin and arylnaphthalene lignans, are leading compounds with important pharmacological properties and a wide range of biological activities. While the first group is well studied mainly for the production of podophyllotoxin, for arylnaphthalene lignans, the data on the availability of a sustainable resource for their production is are still insufficient. The Linum genus, comprising approximately 180 species, is notable for its arylnaphthalene lignans production like justicidin B and isojusticidin B. The pharmacological potential of arylnaphthalene lignans includes cytotoxic, antiviral, anti-inflammatory and antiprotozoal effects. The review highlights the use of biotechnology by in vitro cultures for optimising lignan production. Structural elucidation of novel lignans underscores the ongoing diversity and potential discoveries in this botanical domain, providing an important additional information of arylnaphthalene lignans.